2018
DOI: 10.1534/g3.118.200288
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudokinase Domain of Saccharomyces cerevisiae Tra1 Is Required for Nuclear Localization and Incorporation into the SAGA and NuA4 Complexes

Abstract: Tra1 is an essential component of the SAGA/SLIK and NuA4 complexes in S. cerevisiae, recruiting these co-activator complexes to specific promoters. As a PIKK family member, Tra1 is characterized by a C-terminal phosphoinositide 3-kinase (PI3K) domain. Unlike other PIKK family members (e.g., Tor1, Tor2, Mec1, Tel1), Tra1 has no demonstrable kinase activity. We identified three conserved arginine residues in Tra1 that reside proximal or within the cleft between the N- and C-terminal subdomains of the PI3K domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
63
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(77 citation statements)
references
References 90 publications
(147 reference statements)
13
63
1
Order By: Relevance
“…Supporting these data, polyQ expression sensitized cells to stresses that result in slow growth of strains carrying TRA1 mutations, i.e. calcofluor white, growth at 39°C, 5% ethanol, MMS and caffeine 59 (Figure 2C). Expression of expanded polyQ proteins was also associated with decreased activity from SAGA regulated promoters ( HIS4 and PHO5 ) (Figure 2D) and histone H3 acetylation (Figure 2E), implicating that polyQ affects SAGA function in yeast.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…Supporting these data, polyQ expression sensitized cells to stresses that result in slow growth of strains carrying TRA1 mutations, i.e. calcofluor white, growth at 39°C, 5% ethanol, MMS and caffeine 59 (Figure 2C). Expression of expanded polyQ proteins was also associated with decreased activity from SAGA regulated promoters ( HIS4 and PHO5 ) (Figure 2D) and histone H3 acetylation (Figure 2E), implicating that polyQ affects SAGA function in yeast.…”
Section: Resultsmentioning
confidence: 53%
“…Increased transcription was also observed from promoters of other components of SAGA and NuA4, i.e. NGG1 , SPT7 and EAF1 , but not for the control gene PGK1 as was the case for tra1 59 (Figure 4A). We also observed that the polyQ-induced increase in TRA1 expression was abolished when cells expressing 72Q were treated with the HDAC inhibitor trichostatin A (TSA) (Figure 4B), suggesting that changes in chromatin remodeling the regulate TRA1 expression in the presence of polyQ expansion.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations